Separation of Methane and Carbon Dioxide Gas Mixtures Using Activated Carbon Modified with 2‐Methylimidazole. Issue 9 (10th August 2018) - Zhang, Xiao-Xin; Xiao, Peng; Chen, Guang-Jin; Sun, Chang-Yu; Yang, Lan-Ying
Abstract: Activated carbon was modified by loading 2‐methylimidazole (mIm), ethanol, and glycol onto its surface and adopted to capture CO2 using the absorption‐adsorption method. The modified activated carbon showed high selectivity for separating CH4 +CO2 gas mixtures, compared with other methods to modify activated carbon given in the literature. The separation factor was 4.75 times higher than that for the fresh activated‐carbon system, and the separation performance of the activated carbon increased with increasing amount of mIm. The addition of glycol showed greater potential to enhance the selectivity of the activated carbon than ethanol. A recycling test verified the stability of the modified activated carbon for CH4 +CO2 gas mixture separation. Abstract : 2‐Methylimidazole, ethanol, and glycol are proposed for the modification of activated carbon for use in the separation of CH4 +CO2 gas mixtures. The selectivity coefficient of the modified activated carbon was about five times higher than that of the fresh activated carbon. The CO2 capture mechanism of 2‐methylimidazole and glycol is outlined.